2023
DOI: 10.1002/aur.3018
|View full text |Cite
|
Sign up to set email alerts
|

High definition transcranial direct current stimulation of the Cz improves social dysfunction in children with autism spectrum disorder: A randomized, sham, controlled study

Yonglu Wang,
Fei Wang,
Yue Kong
et al.

Abstract: The purpose of this study was to determine the effect of the Cz of high‐definition 5‐channel tDCS (HD‐tDCS) on social function in 4–12 years‐old children with autism spectrum disorder (ASD). This study was a randomized, double‐blind, pseudo‐controlled trial in which 45 ASD children were recruited and divided into three groups with sex, age, and rehabilitation treatment as control variables. Each group of 15 children with ASD was randomly administered active HD‐tDCS with the Cz as the central anode, active HD‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…One neuromodulation study conducted with participants with social interaction disorders used TENS and reported no adverse events ( Foldes et al, 2021 ). Three studies used tDCS in patients with ASD and reported no adverse events as well as low drop-out rates ( D’Urso et al, 2015 , 2022 ; Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…One neuromodulation study conducted with participants with social interaction disorders used TENS and reported no adverse events ( Foldes et al, 2021 ). Three studies used tDCS in patients with ASD and reported no adverse events as well as low drop-out rates ( D’Urso et al, 2015 , 2022 ; Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…One neuromodulation study conducted with participants with social interaction disorders used TENS and reported no adverse events (Foldes et al, 2021). Three studies used tDCS in patients with ASD and reported no adverse events as well as low drop-out rates (D'Urso et al, 2015(D'Urso et al, , 2022Wang et al, 2023).…”
Section: Feasibility Of Neuroscience-based Intervention Approaches In...mentioning
confidence: 99%